Impacts of globalization on adolescents’ behavior in Malaysia - Azhar Jaafar @ Ramli; Syafril, Syafrimen; Faisal; Engkizar; Anwar, Fuady; Hakim, Rosniati (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article is the result of a study on youth understanding and perception of globalization and its impact on adolescent behavior change from a variety of perspectives including character and emotion, fashion and style, family and social relations. The study conducted using this cross sectional quantitative design involved 482 selected informants using simple random sampling techniques from 37 locations in the FELDA region of Pahang, Malaysia. Data were collected using the questionnaire “Perceptions and knowledge of globalization and the impact of adolescent behavior change” through the process of face validity and content. In addition, data were analyzed using SPPS version of Social Science (SPSS) version 22.0. The results of the analysis show that adolescents maintain a high level of understanding of globalization while maintaining a low level of perception. The findings of the study also show that globalization has a low impact on adolescent behavior change. The results of this study have also been discussed with various theories and previous studies.